A case of right-sided Bochdalek hernia incidentally diagnosed in a gastric cancer patient. Issue 1 (December 2016) - Kikuchi, Satoru; Nishizaki, Masahiko; Kuroda, Shinji; Kagawa, Shunsuke; Fujiwara, Toshiyoshi
Abstract Background Bochdalek hernia (BH) is generally congenital, presenting with respiratory distress. However, this pathology is rarely detected in adults. Some adult cases of BH present with symptoms attributed to the hernia, but incidental detection of BH is increasing among asymptomatic adults due to advances in imaging modalities. This report presents the management of incidental BH patients detected in the preoperative period of gastric cancer. Case presentation An asymptomatic 76-year-old woman was diagnosed with advanced gastric cancer during follow-up after radiotherapy for uterine cervical cancer. Computed tomography (CT) was performed to exclude metastatic gastric cancer, incidentally detecting right-sided BH. We planned distal gastrectomy with lymph node dissection for gastric cancer and simultaneous repair of BH using a laparoscopic approach. We performed laparoscopic gastrectomy for gastric cancer and investigated the right-sided BH to assess whether repair during surgery was warranted. Herniation of the liver into the right hemithorax was observed, but was followed-up without surgical repair because the right hepatic lobe was adherent to the remnant right anterior hemidiaphragm and covered the huge defect in the right hemidiaphragm. No intra- or postoperative pneumothorax was observed during pneumoperitoneum. Conclusion Regardless of symptoms, repair of adult BH is generally recommended to prevent visceral incarceration. However, BH in asymptomatic adults appears to be more common than previously reported in the literature. Surgeons need to consider the management of incidental BH encountered during thoracic or abdominal surgery.